2010
DOI: 10.3390/s100201326
|View full text |Cite
|
Sign up to set email alerts
|

A Lanthanide-Based Chemosensor for Bioavailable Fe3+ Using a Fluorescent Siderophore: An Assay Displacement Approach

Abstract: The measurement of trace analytes in aqueous systems has become increasingly important for understanding ocean primary productivity. In oceanography, iron (Fe) is a key element in regulating ocean productivity, microplankton assemblages and has been identified as a causative element in the development of some harmful algal blooms. The chemosenor developed in this study is based on an indicator displacement approach that utilizes time-resolved fluorescence and fluorescence resonance energy transfer as the sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…This siderophore-based biosensor is cheap, userfriendly, and simple as it relies only on spectrophotometer (Gupta et al 2008). Another study suggested the use of the fluorescent siderophore derivative MA-DFB to act as a photoactive sensor for the biologically available iron content in aquatic systems (Orcutt et al 2010). Although some of the siderophores have been used as potential biosensors, most of them have not yet been characterized.…”
Section: Siderophore As Potential Biocontrol Agentmentioning
confidence: 99%
“…This siderophore-based biosensor is cheap, userfriendly, and simple as it relies only on spectrophotometer (Gupta et al 2008). Another study suggested the use of the fluorescent siderophore derivative MA-DFB to act as a photoactive sensor for the biologically available iron content in aquatic systems (Orcutt et al 2010). Although some of the siderophores have been used as potential biosensors, most of them have not yet been characterized.…”
Section: Siderophore As Potential Biocontrol Agentmentioning
confidence: 99%
“…Once the analyte associated with the binding site, a microenvironment modulation would occurs thus further perturbs the properties of the signaling site and results in producing an obvious change with sensitive signal readout such as optical or electrochemical responses. To date, many unique indicators with bullish "signaling sites" and synthetic receptors containing potential "binding sites" have been extensively used to construct IDA based colorimetric sensors for different objectives including anions [4], cations [5] and biomolecules [6,7] and so on [8]. Due to a sensitive modulated signal, those IDA based colorimetric sensors have explored many advantages such as sensitive color change, easy and convenient to control, and works well in aqueous and organic media.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, considerable efforts have been devoted to the development of Fe 3+ ‐selective sensors. Unfortunately, there have been relatively few fluorescent chemosensors for ferric ; this may be due to its paramagnetic nature which leads to their fluorescence quenching . Therefore, the development of new ‘turn‐on’ fluorescent Fe 3+ indicators, especially those that exhibit selective Fe 3+ ‐amplified emission in aqueous media with color changes, is still a challenge and significant.…”
Section: Introductionmentioning
confidence: 99%